Sejarah Agama Hindu Dan Perkembangannya - siti khodijah dijah (Al Hikmah, 2023)
ABSTAK Hinduism is the religion that has the longest age and is the first religion known to mankind. This description will explain when and where religion was revealed and a brief description of the process of its development. Hinduism is a religion that has given birth to a very complex culture in the fields of astronomy, agriculture, philosophy and other sciences. Because of the wide and too detailed range of exposures of Hinduism, it sometimes feels difficult to understand. Many experts in the field of religion and other sciences have studied Hinduism so that various interpretations and analyzes of Hinduism have emerged. Until now there has been no agreement among experts to determine when Hinduism was revealed, as well as the method and mission of its spread has not been widely understood. The appearance of Hinduism which gives quite a high degree of freedom in carrying out its ceremonies has resulted in many experts who write about this religion that is not in accordance with what is actually in Hinduism. For example: "There are still many experts who write that Hinduism is a polytheistic religion and all kinds of judgments are very uncomfortable, and detrimental to Hinduism". Besides that, even among Hindus, there are still many inaccurate understandings of religious teachings that are understood and practiced. Thus the purpose of this paper is to help straighten out deviant opinions and unclear understandings of the real thing about Hinduism.